Sustainable Rice Straw Management 2019
DOI: 10.1007/978-3-030-32373-8_4
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical Conversion of Rice Straw

Abstract: Biomass conversion into various forms of energy, such as heat, power, or biofuels using thermal processes, involves the decomposition of biomass by exposure to heat, typically above 300 °C. Thermal conversion processes include pyrolysis, gasification, and direct combustion. Several factors affect the yields and energy recovery from these processes including temperature, reaction time, heating rate, absence, or presence of oxygen, use of catalysts, and pressure. Due to rice straw's relatively high carbon and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 64 publications
(61 reference statements)
0
6
0
2
Order By: Relevance
“…Therefore, proper controlling measures must be implemented to prevent such releases into the atmosphere. Accordingly, several research studies had suggested that a pretreatment stage of feedstock (i.e., drying, shredding) prior to combustion could influence the process efficiency as compared to the direct combustion process [ 40 , 49 ].…”
Section: Production Technologies Of Food Waste–based Biocharmentioning
confidence: 99%
“…Therefore, proper controlling measures must be implemented to prevent such releases into the atmosphere. Accordingly, several research studies had suggested that a pretreatment stage of feedstock (i.e., drying, shredding) prior to combustion could influence the process efficiency as compared to the direct combustion process [ 40 , 49 ].…”
Section: Production Technologies Of Food Waste–based Biocharmentioning
confidence: 99%
“…Penelitian Nam et al, (2016) Kadar N yang dihasilkan untuk fresh dan used baglog yaitu 0,82% dan 0,83%. Berdasarkan Maguyon-Detras et al, (2020), disebutkan bahwa batas kadar N pada biomassa jerami sebesar 0,8-1,4%. Hal ini menyatakan bahwa, kadar N fresh dan used baglog masih sesuai standar.…”
Section: Ultimate (%)unclassified
“…The selection of appropriate technology for material conversion is largely dependent on its moisture content and its physical, mechanical, and chemical composition criteria [ 111 ]. In particular, biomass materials can have moisture contents as high as 95% by weight and still be suitable for combustion with a supercritical water process.…”
Section: Valorization Of Rice Residuesmentioning
confidence: 99%